Application of the SIKOPDIT Accounting Application in Improving the Financial Administration Efficiency of KSP Kopdit Ikamala - Agustina Nona Mathilda; Andreas Rengga; Maria Nona Dince (Neo Journal of economy and social humanities, 2025)
This study aims to analyze the application of SIKOPDIT accounting application in improving the efficiency of financial administration in the Kopdit Ikamala's Savings and Loan Cooperative (KSP). The method used in this study is a qualitative descriptive approach, with data collection techniques through observation, interviews, and document analysis. The results of the study show that the implementation of the SIKOPDIT application has a positive impact on improving the efficiency of cooperative financial administration. Before the application was implemented, the transaction recording process was carried out manually, making it prone to errors and delays in preparing financial statements. With SIKOPDIT, transaction recording can be done in real time, reducing human errors, accelerating the financial reconciliation process, and improving the quality of financial statements. In addition, this system provides better transparency in the financial management of cooperatives. However, the implementation of this application also faced obstacles, especially in the form of resistance from some staff who were used to manual methods. This obstacle is overcome through intensive training and mentoring so that staff can better understand the use of the system. Overall, this study emphasizes that digital transformation through accounting applications is a strategic step in improving cooperative operational efficiency, which can ultimately strengthen member trust and encourage cooperative growth. This study implies that the application of the SIKOPDIT application has been proven to be able to improve work efficiency in financial administration, especially in terms of recording transactions, preparing financial statements, and monitoring member data. This can encourage KSP Kopdit Ikamala to continue to optimize the use of digital technology in all operational processes to increase productivity and service to members.